2007
DOI: 10.1002/ijc.23232
|View full text |Cite
|
Sign up to set email alerts
|

Trends in oesophageal cancer incidence and mortality in Europe

Abstract: To monitor recent trends in mortality from oesophageal cancer in 33 European countries, we analyzed the data provided by the World Health Organization over the last 2 decades, using also joinpoint regression. For selected European cancer registration areas, we also analyzed incidence rates for different histological types. For men in the European Union (EU), age-standardized (world population) mortality rates were stable around 6/100,000 between the early 1980s and the early 1990s, and slightly declined in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
165
1
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(182 citation statements)
references
References 31 publications
(31 reference statements)
10
165
1
6
Order By: Relevance
“…Case-control studies conducted in Brazil have demonstrated that other factors may contribute to EC in addition to ethylism and tabagism, such as excessive pepper intake, intake of wood stove cooking and ingestion of hightemperature yerba mate 6,29,32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Case-control studies conducted in Brazil have demonstrated that other factors may contribute to EC in addition to ethylism and tabagism, such as excessive pepper intake, intake of wood stove cooking and ingestion of hightemperature yerba mate 6,29,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal cancer incidence is greater in individuals over 50 years of age due to the prolonged action of aggressive factors 6 . In the present study, the mean patient age was 60.3 ± 10.6 years (for SCC) and 62 ± 11.5 years (for ADC) without difference between them (p = 0.31).…”
Section: Survival Ratementioning
confidence: 99%
See 1 more Smart Citation
“…The incidence in Iran, south-central regions of the former Soviet Union, Afghanistan, Mongolia and northwest China is 10 times higher than in other countries. Annually 160 cases the esophageal cancer per 100,000 population in Iran, in other countries including North America, Europe, and Japanfrom four to eight cases (Zambon, 2000;Yankin, 2003;Bosetti et al, 2008;Krutilina, 2008;Davydov et al, 2009;Ferlay et al, 2010;Zhao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In the United States from 1975 to 2001, the incidence of EAC rose from 4 to 23 cases per million. 4 In the United Kingdom, a similar increase in EAC 5 is observed, although the absolute incidence is much higher than in the United States.…”
mentioning
confidence: 99%